EVALUASI KEBIJAKAN PELAKSANAAN PENDAFTARAN PERALIHAN HAK MILIK ATAS TANAH MELALUI JUAL BELI PADA KANTOR PERTANAHAN KOTA PALU - Torangan, Virta Yolanda; Tjaija, Abu; Pasinringi, Andi (Katalogis, 2021)
The purpose of this study; To find out how the policy evaluation of the implementation of the registration of ownership rights over land through buying and selling at the Palu City Land Office Evaluation Theory The policy used in this research is the theory of William DUNN, the basis and type of research is qualitative, while the type of research is descriptive, informant determination technique conducted purposively on the land office officials of the City of Palu. The technique of data collection is done by interview, observation, and documentation. While the data analysis technique used is the Miles Huberman model, which is carried out in three stages, namely; Data reduction, data presentation and conclusion or verification. Based on the background of the research and the formulation of the problem, as well as the results of research and discussion using a theoretical reference from William DUNN, with the dimensions of Effectiveness, Efficiency, Adequacy, Equity of Responsiveness, and Accuracy, the results of the study can be concluded: Through buying and selling, it has not been effective, because from the six {6} evaluation dimensions of William DUNN have not been optimally fulfilled, because the targets set are not in accordance with the reality that occurs.